A Newly Developed Indicator of Overeating Saturated Fat Based on Serum Fatty Acids and Amino Acids and Its Association With Incidence of Type 2 Diabetes: Evidence From Two Randomized Controlled Feeding Trials and a Prospective Study - Wei, Wei; Zi, Tianqi; Yang, Ruiming; Xu, Jiaxu; Chen, Yunyan; Jiang, XiTao; Chu, Xia; Yang, Xue; Jiang, Wenbo (Frontiers in Nutrition, 2022)
Objective Hyper-caloric intake of saturated fatty acids(SFA) is common in modern societies, probably contributing to the epidemic of type 2 diabetes mellitus(T2DM). This study conducted two randomized controlled trials(RCT) for developing a new indicator that can assess the nutritional status, and examined its association with incidence of T2DM. Methods In RCT-1, healthy participants were randomly assigned into three groups: control group(n=40), overfeeding-group 1(100g butter per day, n=37), and overfeeding-group 2(120g butter per day, n=37). In RCT-2, healthy subjects were randomly assigned into two groups: control group(n=52) and high fat group (300-extra kcal/d from diet that was designed by high fat diet, n=58). In the prospective-cohort, 4057 participants aged 20-74 year-old were enrolled and followed up over 5.3-year. Serum-profiles of fatty-acids and amino-acids were measured. Results In RCT-1, serum fatty-acids including C14:0 and C18:0 increased, whereas C18:2, C20:4, C22:5, and C22:6 decreased; serum amino-acids including tyrosine, alanine, and aminobutyric-acid increased, whereas histidine and glycine decreased (P<0.05). Among these serum fatty-acids and amino-acids, changes in C14:0, C20:4, tyrosine, histidine and glycine were also observed in the RCT-2. An indicator was developed based on the five fatty-acids and amino-acids: C14:0*tyrosine*1000/[C20:4*(glycine+histidine)], and it significantly identified participants in the intervention-group with AUC(95%CI) being 0.85(0.77-0.92). The indicator was significantly associated with incidence of T2DM in the prospective-cohort with HRs(95%CIs) from bottom-quartile to top-quartile being 1, 1.26(0.87-1.83), 1.78(1.25-2.53), 2.35(1.65-3.34). Conclusion The newly developed indicator in RCTs can be used in assessing the nutritional-status of hyper-caloric intake of SFA and predicting the development of T2DM.